2022
DOI: 10.1002/joc.7862
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal characteristics of near‐surface air temperature across local climate zones in a tropical city

Abstract: The present study examines the temporal and spatial variability of near-surface air temperature and the canopy layer urban heat island (UHI) in Singapore.Observations collected at 20 locations across the island city-state and during 6 years make this one of the most extensive studies carried out in a tropical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 57 publications
5
20
0
2
Order By: Relevance
“…The analysis focuses on the 10 most populous cities, which are reported in Table 1 along with a selection of their characteristics; while at the end of the paper Figure A1 presents maps of the cities and their surroundings. Roth et al (2022) observed that the choice of 'rural' reference has a significant impact on the nighttime UHI magnitude, with differences of up to 2 C. Section 3 corroborates this observation illustrating that the choice of a location based solely on the presence of a measurement tower can result in UHI values off by more than 2 C. For these reasons, reference rural cells have been selected in order to be as uniform as possible across the cities analysed. This selection takes into account the LCZ composition of each cell, as illustrated in Figure 2 which presents the composition of both the city centre (middle panel) as well as that of the grid cell selected for the rural reference (bottom panel).…”
Section: Study Areamentioning
confidence: 61%
See 1 more Smart Citation
“…The analysis focuses on the 10 most populous cities, which are reported in Table 1 along with a selection of their characteristics; while at the end of the paper Figure A1 presents maps of the cities and their surroundings. Roth et al (2022) observed that the choice of 'rural' reference has a significant impact on the nighttime UHI magnitude, with differences of up to 2 C. Section 3 corroborates this observation illustrating that the choice of a location based solely on the presence of a measurement tower can result in UHI values off by more than 2 C. For these reasons, reference rural cells have been selected in order to be as uniform as possible across the cities analysed. This selection takes into account the LCZ composition of each cell, as illustrated in Figure 2 which presents the composition of both the city centre (middle panel) as well as that of the grid cell selected for the rural reference (bottom panel).…”
Section: Study Areamentioning
confidence: 61%
“…The Chasseral finally explains the negative two-point-delta UHI values reported for Biel: the forest-covered slope of the mountain pushes the peak of UHI south east of the geographical city centre (depicted in Figure A1j) which has been used as reference for the UHI calculations. This illustrates the difficulty in selecting references for two-point-delta UHI, highlighted by Roth et al (2022) for Singapore. Qualitatively, most cities present a UHI map which is not round in shape, helping with a geographical dispersion of the UHI intensity, as discussed by Zhou et al (2017).…”
Section: Urban Heat Islandmentioning
confidence: 99%
“…For the case of the city-state of Singapore, ten flux towers would be needed to cover the about ten different Local Climate Zones ( i.e. , different r H values) that make up the majority of the urban sprawl, 72 assuming that a flux tower can be installed in each LCZ, and the variability in ambient concentrations of the trace gas of interest among them is not significant. About 150 coordinated mobile units would be also required, assuming that each could cover two of the 330 neighborhoods of the city during 1 hour sampling periods.…”
Section: In Closingmentioning
confidence: 99%
“…Due to this interaction, seasonal differences in UHI intensity, could potentially alter the sea breeze onset and propagation speed (Wang et al, 2019;Yoshikado, 1992). Such seasonal differences in UHI-intensity in MC's tropical city have been demonstrated through extensive observation in Singapore (Chow & Roth, 2006;Roth et al, 2022). Their result shows consistently higher UHI intensity during dry season compared to rainy season.…”
Section: Introductionmentioning
confidence: 97%